2016
DOI: 10.1515/ling-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Attraction between words as a function of frequency and representational distance: Words in the bilingual brain

Abstract: Bilingual speakers store cognates from related languages close together in their mental lexicon. In the case of minority languages, words from the dominant language often exert influence on their cognates in the minority language. In this article, we present a model describing that influence or force of attraction as a function of frequency and of (dis)similarity (representational distance). More specifically, it is claimed that the strength of the force of attraction of one word upon another is (among others)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Therefore, representations of cognates such as Wasser 'water' [ˈvasɐ] in Standard German and its Swiss-German equivalent [ˈʋasːəʁ] could be more entrenched and more accessible, which in turn eases production. This is related to the findings of Versloot and Hoekstra (2016), who showed that frequency and phonological similarity of words exert an influence on their cognates in the weaker language. Similarity of form and concept might serve a booster function in terms of conceptual and/or phonological bootstrapping (Carey, 2011;Vihman and Croft, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, representations of cognates such as Wasser 'water' [ˈvasɐ] in Standard German and its Swiss-German equivalent [ˈʋasːəʁ] could be more entrenched and more accessible, which in turn eases production. This is related to the findings of Versloot and Hoekstra (2016), who showed that frequency and phonological similarity of words exert an influence on their cognates in the weaker language. Similarity of form and concept might serve a booster function in terms of conceptual and/or phonological bootstrapping (Carey, 2011;Vihman and Croft, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Basque was found to be used in 9.4% of the interactions, whereas Spanish was used in 87.4% (Altuna, 2016). The linguistic items that are used frequently have stronger representations and are easier to access and process (Bybee, 1995;Diessel, 2007;Versloot and Hoekstra, 2016). The bilinguals have both Basque and Spanish predicative constructions in their repertoire.…”
Section: Why the Choice Of Spanish Word Order Pattern?mentioning
confidence: 99%
“…As Spanish is used more, the Spanish construction is repeated more frequently, which leads to a stronger cognitive representation and a deeper entrenchment of this pattern in the bilingual mind. Both frequency and similarity -the analogies that the speakers draw between constructions -contribute to the force of attraction (Versloot and Hoekstra, 2016). The prototypical predicative Spanish and Basque constructions are structurally relatively similar: they consist of a (often dropped pronominal) subject, a predicative, and a copula verb.…”
Section: Why the Choice Of Spanish Word Order Pattern?mentioning
confidence: 99%
“…In addition, frequency also provides psycholinguistic information about the cognitive neural network representing language. A word's frequency is a reliable measure of the strength of its neural representation (Bybee 1995:452;Versloot & Hoekstra 2016:1225-1226, since frequent items are accessed and processed faster and more reliably (Diessel 2007). In the competition between linguistic variants of any sort, frequency of occurrence adds to competitive strength (Krott, Baayen, & Schreuder 2001).…”
Section: Competition and Changementioning
confidence: 99%